Konsep Adab dalam Pendidikan Islam: Relevansinya di Era Postmodern - Ai Reni Ratnasari; Ujang Miftahudin (TA'DIB: Jurnal Pendidikan Agama Islam, 2025)
This research examines the concept of adab in Islamic education and its relevance in the postmodern era marked by value crises, moral relativism, and deconstruction of traditional authority. The concept of adab in Islam includes not only modesty in behavior, but also the glorification of knowledge, respect for teachers, and awareness of spiritual and social responsibility. In the framework of the thinking of figures such as Syed Muhammad Naquib al-Attas, adab is the core of true Islamic education. Through a qualitative approach based on literature studies, this study analyzes classical and contemporary literature to explore the meaning, purpose, and application of adab in education. The results of the study show that the values of manners are still very relevant in the midst of the challenges of the postmodern era, especially in shaping the character of students that are holistic and rooted in transcendental values. The integration of manners in the contemporary education system is seen as a solution to the spiritual void and ethical crisis that colors the times.